Enhanced choline and Rb+ transport in human erythrocytes infected with the malaria parasite Plasmodium falciparum. - Kirk, K; Wong, H; Elford, B; Newbold, C; Ellory, J (1991)
Human erythrocytes infected in vitro with the malaria parasite Plasmodium falciparum showed a markedly increased rate of choline influx compared with normal cells. Choline transport into uninfected cells (cultured in parallel with infected cells) obeyed Michaelis-Menten kinetics (Km approximately 11 microM). In malaria-parasite-infected cells there was an additional choline-transport component which failed to saturate at extracellular concentrations of up to 500 microM. This component was less sensitive than the endogenous transporter to inhibition by the Cinchona bark alkaloids quinine, quinidine, cinchonine and cinchonidine, but showed a much greater sensitivity than the native system to inhibition by piperine. The sensitivity of the induced choline transport to these reagents was similar to that of the malaria-induced (ouabain- and bumetanide-resistant) Rb(+)-transport pathway; however, the relative magnitudes of the piperine-sensitive choline and Rb+ fluxes in malaria-parasite-infected cells varied between cultures. This suggests either that the enhanced transport of the two cations was via functionally distinct (albeit pharmacologically similar) pathways, or that the transport was mediated by a pathway with variable substrate selectivity.